2020
DOI: 10.1111/nhs.12751
|View full text |Cite
|
Sign up to set email alerts
|

Body size dissatisfaction associated with dietary pattern, overweight, and physical activity in adolescents: A cross‐sectional study

Abstract: This study analyzed the association of body size dissatisfaction with body mass index, dietary pattern, and physical activity in adolescents. A sample of 1074 participants between 10 and 17 years of age was recruited. Body size dissatisfaction was assessed with the silhouettes' scale. Dietary pattern, physical activity, and socioeconomic status were assessed with questionnaires. Body mass index was measured objectively. The prevalence of body size dissatisfaction was 77.0%, where 29.8% desired to increase body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
(43 reference statements)
1
13
0
1
Order By: Relevance
“…Nonetheless, adolescents who engaged in weight control practices could be disappointed with the outcome if their expectations to achieve societal beauty standards are not met [ 80 ], leading to BD. These weight control practices were similar to previous studies [ 15 , 16 , 28 , 29 ].With respect to sex, Radwan et al conducted a study on Emirati University students proposed that female students who wanted to be thinner preferred following a diet for weight loss, whereas males who desired to be heavier were physically active and less likely to follow a diet [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, adolescents who engaged in weight control practices could be disappointed with the outcome if their expectations to achieve societal beauty standards are not met [ 80 ], leading to BD. These weight control practices were similar to previous studies [ 15 , 16 , 28 , 29 ].With respect to sex, Radwan et al conducted a study on Emirati University students proposed that female students who wanted to be thinner preferred following a diet for weight loss, whereas males who desired to be heavier were physically active and less likely to follow a diet [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of BD is growing at alarming rates both globally [ 13 – 15 ] and regionally [ 5 , 16 18 ]. A recent study among 308 Emirati University students between 18 and 25 years old showed that 81% of them had BD [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the importance of achieving a healthy body weight, there is a growing body of research that focused on factors associated with the perception of body weight throughout the world (Amaro‐Rivera & Carbone, 2020; Caleyachetty et al, 2016; Colchero et al, 2014; Jang et al, 2018; Kye & Park, 2021; Park et al, 2019; Sabiston et al, 2019; Tebar et al, 2020; Tsuchiya et al, 2019; Wan Abdul Hamed & Abd Aziz, 2020). Most of these studies found significant relationships between sociodemographic factors, such as age, income and education, and body weight perception, but they focused only on developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 81% of adolescent girls living with OW/OB reported being dissatisfied with their body size compared to 45% of underweight and 52% of normal weight [ 10 ]. The aspiration to reduce body size has been associated with obesity-related behaviors such as poor sleep [ 16 ] and low consumption of fruits and vegetables [ 17 ]. BSD has also been shown to behave as both a motivation and barrier to PA [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%